AN IMPROVED METHOD FOR ISOLATION OF THIELAVIOPSIS PARADOXA FROM STEM BLEEDING AFFECTED COCONUT PALMS - Anil Kumar; K.K.N. Nambiar (International Coconut Community Journal, 1991)
Stem bleeding of coconut caused by Thielaviopsis paradoxa (de Seynes) Von Hohnel is an important disease affecting coconut in many countries (Menon and Pandalai, 1958; Ohler, 1966, Nambiar and Sastry, 1988). lsolation of the pathogen from diseased tissues on different agar based media has given inconsistent results (Anon., 1976; Anon., 1986), None of the selective media reported for certain related fungi viz., T. basicola (Berk and Br.) Ferr. (David, 1978;Tsao and Bricker, 1966) and Ceratocystis wagnerii Goheen and Cobb (Hicks et al., 1980) proved useful for the isolation of T. paradoxa Since, standardization of an isolation method is a basic necessity for any study on plant pathogens, an attempt was made to improve upon existing methods.